Costos de implementación BIM según su nivel de uso en planificación y diseño en la construcción en Ecuador - Guzmán Paca, César Pachakutik (2025)
Building Information Modeling (BIM) has become an essential tool in the architecture, engineering, and construction (AEC) industry, improving coordination, efficiency, and project accuracy. However, in Ecuador, its adoption faces significant challenges, such as high initial costs, technological limitations, and a lack of regulatory standardization. This study examines the costs of companies implementing BIM in the planning and design phases of construction projects, considering the level of use in nine companies from various provinces in Ecuador. The BIM Use Assessment (BUA) tool and structured interviews were used to classify BIM usage levels and quantify costs in three categories: personnel capacity, technological capacity, and physical space. The results conclude that implementing BIM at advanced levels is feasible without substantial increases in adoption costs. This work establishes an innovative framework for evaluating the economic viability of BIM in developing economies by analyzing the associated costs. Additionally, it proposes strategies to overcome current barriers and promote adoption, with significant implications for future comparative studies and contributions to regional research in Latin America.